Silver coated cathode for molten carbonate fuel cells. (31st July 2020) - Lysik, A.; Wejrzanowski, T.; Cwieka, K.; Skibinski, J.; Milewski, J.; Marques, F.M.B.; Norby, T.; Xing, W.
Abstract: Within this study, a layered cathode for use in a Molten Carbonate Fuel Cell (MCFC) has been developed. The substrate layer and reference MCFC cathode made of porous nickel was covered by a porous silver film with defined porosity and pore size. Both layers were fabricated using the tape casting method and further fired in a reductive atmosphere. The new cathode was assembled with other reference cell components to form a single MCFC, which was subjected to performance and durability tests. Scanning electron microscopy was used to analyze the microstructure of the materials before and after tests. The reference cathode was also studied for the comparison. The results show that the porous silver layer was able to enhance the electron transport between the cathode and current collector. It was also found that oxygen reduction is enhanced due to the presence of silver in the gas supply. As a result, the power density of the cell was increased by 50%. On the other hand, due to the separation from electrolyte by the NiO layer, no significant degradation of the silver layer, identified by SEM or electrochemical tests, was found after 1000 h. Highlights: The chemical composition of the MCFC cathode was modified. A layer of silver was applied by the tape-casting method. The effect of silver addition on MCFC performance was investigated. Contact resistance between the cathode and current collectors has been reduced. The presence of silver increases the maximum power density obtained.